2018
DOI: 10.1111/zsc.12296
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive phylogeny of the laughingthrushes and allies (Aves, Leiothrichidae) and a proposal for a revised taxonomy

Abstract: DNA phylogenies have gradually shed light on the phylogenetic relationships of the large babbler group. We focus in this study on the family Leiothrichidae (laughingthrushes and "song babblers"), which represents the largest clade of babblers in terms of species diversity. Our phylogeny includes all genera and 82% of the recognized species, using mitochondrial and nuclear loci. The sister group to Leiothrichidae is composed of the Pellorneidae ("jungle babblers") plus the genus Alcippe. Within Leiothrichidae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
(63 reference statements)
4
17
1
Order By: Relevance
“…Recent classification studies have split this family into five discrete families 13 . Three of them, Leiothrichidae, Pellorneidae and Timaliidae consisted of traditional babblers while Zosteropidae that included mainly Yuhina and some other minor species, and Sylviidae grouped all the Sylvia warblers 14 . Among these five distinct families, Leiothrichidae is the largest consisting of 125 species distributed mainly in the Sino-Himalayan and South-Eastern parts of Asia 14 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent classification studies have split this family into five discrete families 13 . Three of them, Leiothrichidae, Pellorneidae and Timaliidae consisted of traditional babblers while Zosteropidae that included mainly Yuhina and some other minor species, and Sylviidae grouped all the Sylvia warblers 14 . Among these five distinct families, Leiothrichidae is the largest consisting of 125 species distributed mainly in the Sino-Himalayan and South-Eastern parts of Asia 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Three of them, Leiothrichidae, Pellorneidae and Timaliidae consisted of traditional babblers while Zosteropidae that included mainly Yuhina and some other minor species, and Sylviidae grouped all the Sylvia warblers 14 . Among these five distinct families, Leiothrichidae is the largest consisting of 125 species distributed mainly in the Sino-Himalayan and South-Eastern parts of Asia 14 . A study on the Leiothrichidae family suggested their origin prior to the Miocene–Pliocene boundary, which is well known for its noteworthy climatic turmoil in Asia 13 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations